Pemanfaatan Sosial Media Marketing Dalam Upaya Meningkatkan Penjualan Umkm Pada Produk Bubuk Kopi Robusta (Gubuk Angin) Di Kecamatan Bumiaji Kota Batu - Miftahul Zanna Arsyad; Muh K Bonesaputra Rukman; Agung Winarno; Agus Hermawan (Pusat Riset dan Inovasi Nasional, 2022)
UMKM use the internet as an online marketing tool to gain a satisfying market share. Everyone in the world has easy access to the internet, including MSME entrepreneurs who have used the internet as a medium for providing and developing information sharing about products offered to consumers online. The purpose of this service is to help businesses use social media as a medium for selling Robusta ground coffee products (Gubuk Angin) in Bumiaji District, Batu City. The method used in this business is to provide attractive packaging improvements, socialize social media marketing, help set up social accounts, and create promotional media such as pictures, photos and videos.